Children’s health insurance coverage in the United States: The role of parents’ ethnicity and immigration status - Swarn CHATTERJEE (Theoretical and Applied Economics, 2016)

(untitled)
This study explores whether parents’ decision to carry health insurance for their children varies by race/ethnicity or immigration status. The results indicate that when compared to the reference group of native-born white parents, foreign-born, Hispanic, and black parents were less likely to have private health insurance coverage and more likely to have public health insurance coverage for their children. The likelihood of being uninsured increased with lower educational attainment, poverty, and status as a single parent, and the likelihood of having public health insurance coverage for children was positively associated with living in poverty, being female, and household size.